The Identity of Coconut Shell Jewelry pertaining to the Group of Coconut Shell Handicraft in the Community of Khao Takhli, Takhli District, Nakhon Sawan Province - Pulek, Samolpan (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2021)
The purpose of researching the identity of coconut shell earrings pertaining to the group of coconut shell handicraft of the community of Hua Khao Takhli, Takhli District, Nakhon Sawan Province is twofold: Firstly, to study and analyze the forms of coconut shell earrings of Hua Khao Takhli community, Takhli District, Nakhon Sawan Province. Secondly, to create and develop earrings made from coconut shells into products that promote and improve the livelihood of handicraft professional groups of the community of Hua Khao Takhli, Takhli District, Nakhon Sawan Province. This study is both a qualitative and quantitative research. The researcher utilized purposive sampling to obtain data which points to the concept behind the design of this product. This design resulted in improvement of way of life for handicraft artisans in the community as it aimed at using materials available within the community and shaping them into products that correspond to current fashion trends. Data collection was carried out via interviewing, surveying and answering questionnaires. Interviewees included three people who were an entrepreneur, a community leader, and a village resident respectively. A survey was given to three product design specialists regarding how well the coconut earrings were designed. Questionnaires that queried about satisfaction toward the design of earrings made from coconut shells were given out to 100 people consisting of sampling group and tourists. The findings were obtained by considering three criteria: design, production, and beauty, in order to determine how well the coconut earring designs reflected the identity of Nakhon Sawan Province. It was found that six jewelry designs met these criteria. They increase value for community merchandise, are acknowledged and in demand by the market, as well as contribute to future business dealings.